Perilaku dan Kekuatan Sambungan Kolom pada Sistem Beton Pracetak - Yuniarto Adi, Rudi; Nurhuda, Ilham; Sukamta, Sukamta; Fitriani, Intan (Department of Civil Engineering, Diponegoro University, 2014)
At this time, the architecture and design of the existing floor plan often changes according to the needs and tastes of the owner in accordance with the changing times. This research was conducted as precast concrete structures become even more important with the increase in man's desire to change the design of his home without spending enormous cost. This study aims to investigate the stiffness and study the behavior of precast concrete between monolith column with no connections and the column with connection. The connection used is dry joint using a plate and screw nut. The results obtained are the stiffness of the test specimen column with no connections is smaller than the test object column with connection. The modulus of elasticity of the column without a connection greater than the column with connection. Cracks that occurred in the test object columns without connection occurs faster than the test object columns with connection and both, flexural cracks occur first and then cracked in shear.